Scouting Interactive Games for Scouts Based on Embodied Interaction Using Embedded System - Wibowo, Iwan Kurnianto; Cahyo, Muhammad Andan (Politeknik Elektronika Negeri Surabaya (PENS), 2021)
Scouts is the scouting level after the cub scout aged 11-15 years old. In their age range, they can use logical thinking in the form of physical objects to solve a problem. The development of the Scout Movement has had ups and downs, and recently the number of children interest in scouting activities decreases. The impact is the scouting insight they get isn't optimal. One strategy to solve this problem is by developed forms, tools, and learning media of scouting. Game is one of the learning media that can be used to create effective learning. The educational game is a popular learning media and widely developed by experts, as well as in Indonesia. Unfortunately, in the field of scouting, educational games are less developed. In this research, the author will build an educational scouting game for scouts. In the scouts level, they began to be introduced about communication code, skills, natural recognition, and others. Games created using Embodied Interaction technology. This technology allows users to control the game using body movement. The purpose of this game is to increase the interest and insight of children on Scout activities. From the results of research that has been done, it can be seen that after playing the game, 95,7% of children thought it is exciting, and 87% of them became enthusiastic join scouting activity. Based on the results of the pre-test and post-test, scouting insight increased after playing the game with an average percentage of increased insight being 18.7%.